Gynaecologic and Systemic Comorbidities in Patients with Endometriosis: Impact on Quality of Life and Global Health - Tommaso Capezzuoli; Gretha Orlandi; Sara Clemenza; Ilaria Ponziani; Flavia Sorbi; Silvia Vannuccini; Felice Petraglia (IMR Press, 2022)
Objectives: Endometriosis is an inflammatory disease characterized by a frequent association with gynecologic and systemic comorbidities. Our aim was to evaluate which gynecologic and systemic comorbidities occur in women affected by endometriosis and their impact on quality of life and global health. Mechanism: A literature search of the PubMed, Cochrane Library, Scopus and Web of Science databases was performed to identify the relevant studies published before December 31, 2021. We selected clinical studies, systematic reviews, and meta-analyses in English. Findings in Brief: Endometriosis is strongly associated with gynecologic (adenomyosis, uterine fibroids, polycystic ovarian syndrome-PCOS) and systemic (autoimmune, inflammatory, psychiatric and neurological disorders) comorbidities that impair women quality of life and global health through multiple mechanisms, influencing everyday life and work activities. Conclusions: Endometriosis is a chronic disease, impairing multiple functioning areas and affecting women's health and everyday life. Considering the co-existence of multiple both gynecological and non-gynecological disorders, endometrisois needs a multidisciplinary approach. Thus, specialized referral centres are warranted for a personalized management, focused on patient symptoms and comorbidities.